Antifungal potential of Bacillus strains: implications for biocontrol strategies in food safety and sustainable agriculture - Gharsallah, Houda; Cheffi, Manel; Mallek, Rahma; Omri, Noura; Triki, Mohamed Ali; Öztop, Mecit Halil; Zarai, Zied (Frontiers in Microbiology, 2025)
IntroductionMicrobial spoilage and fungal phytopathogen infections significantly reduce the shelf life of perishable foods, creating major challenges for both agriculture and food supply chains. Bacillus species are known producers of antifungal metabolites such as lipopeptides and volatile organic compounds (VOCs), offering a sustainable alternative to synthetic fungicides.MethodsThis study evaluated the antagonistic activity of four Bacillus strains, H6 (Bacillus velezensis), S15 and S40 (Bacillus subtilis), and S32 (Bacillus cereus) against nine fungal phytopathogens, including those affecting tomatoes. Assessment methods included 108 dual-culture assays, in vitro lipopeptide bioassays, VOC-mediated inhibition tests, and PCR screening for genes involved in lipopeptide biosynthesis.ResultsStrains H6 and S15 exhibited strong antagonistic effects, inhibiting mycelial growth by up to 78% for Botrytis cinerea (H6) and 87% for S15. Lipopeptide bioassays revealed that purified extracts from H6, S15, and S32 inhibited Rhizoctonia solani mycelial growth by 60%. VOCs produced by all four strains completely inhibited the growth of Fusarium oxysporum and Lasiodiplodia theobromae, with strain S40 showing the strongest VOC-mediated inhibition.DiscussionThese results demonstrate the significant antifungal potential of Bacillus strains H6 and S15, which produce iturin/fengycin-type lipopeptides and VOCs, as supported by PCR detection of biosynthetic genes. These strains represent promising candidates for environmentally friendly strategies in food preservation and agricultural biocontrol.